179k views
4 votes
How do you solve the system of the linear equation by substitution?
y=x-4
4x-y=3

2 Answers

4 votes

Answer: (
-(1)/(3),-(13)/(3)

Explanation:

Substitut (x-4) into the equation of 4x-y=3

(Substitute what y equals into the equation

Make sure to keep parentheses!

That becomes 4x-(x-4)=3

Than you must distribute the negative to x and to -4

When you do it creates the equation of 4x-x+4=3

When combining like terms you get: 3x+4=3

Then solve -4 -4

3x=-1

3 3 x=-1

3

Than substitute the x in for the equation of y=x-4 to find what y equals! since you know that x equals -1/3 than subtract -1/3 - 4 to get

y= -13

3

User Elisaveta
by
4.8k points
2 votes

Answer:

x=-1/3, y=-13/3. (-1/3, -13/3).

Explanation:

y=x-4

4x-y=3

------------

4x-(x-4)=3

4x-x+4=3

3x+4=3

3x=3-4

3x=-1

x=-1/3

y=-1/3-4

y=-1/3-12/3=-13/3

User Ragnarokkr
by
4.8k points